Lama perendaman gigi di dalam air perasan jeruk nipis (Citrus aurantifolia Swingle) mempengaruhi kedalaman porositas mikro email (Duration of immersing teeth in lime (Citrus aurantifolia Swingle) juice affects on microporosity depth of enamel) - Vanda Ayu Kartika Hediana; Niken Probosari; Dyah Setyorini (DiscoverSys Inc., 2015)
Lime juice contains some organic acids. It is a plant that is widely consumed by people.Organic acid content causes the lime has an acidic pH. The consumption of beverages containing excess acid may cause tooth erosion due to demineralizationonenamel surface.Demineralization happens constantly causes the loss of some enamel prismata and formamicroporosityinthe enamel. This research wasconducted to measure the depth of enamel microporosity of the teeth enamel is soaked in limejuice. Samples were maxillary first premolar teeth which were divided into two groups: control (soaked in artificial saliva)and treatment (soaked in lime juice) respectively for 5 and 10 minutes. Depth measurement of enamel microporosity wasmeasuredby using a scanning electron microscope, which showed no significant difference (Î±<0.05) between the depth ofthe microporosity of the enamel were soaked lemon juice for 5 minutes and 10 minutes. It was concluded that the longer thetooth enamel soaking in lime juice causes deeper microporosity.